Topography of callosal atrophy reflects distribution of regional cerebral volume reduction in Alzheimer’s disease - Pantel, Johannes; Schröder, Johannes; Jauß, Jan Marek; Essig, Marco; Minakaran, Ramin; Schönknecht, Peter; Boyen, Georg von; Schad, Lothar R.; Knopp, Michael V. (Psychiatry research, 1999)
It has been suggested that regional corpus callosum atrophy in Alzheimer’s disease (AD) may serve as an in vivo index of neuronal loss in the neocortex. In this study total and regional size of the corpus callosum was evaluated with respect to the volumes of the frontal, temporal, and parietal lobes in 38 patients with AD (NINCDS-ADRDA criteria) using quantitative magnetic resonance imaging. Twenty healthy subjects matched for age and gender served as a control group. All quantitative measurements were performed by manual tracing using personal computer-based software. Both total size and as the five measured regional subsections were significantly smaller in AD when compared to the control subjects. The severity of dementia was significantly correlated with the size of the middle sections of the corpus callosum (rostral body and midbody). Within the AD group, the rostral body of the corpus callosum was significantly correlated with the frontal lobe volumes, the midbody was correlated with the temporal lobe volumes, and size of the splenium was correlated with the parietal lobe volumes. We conclude that callosal atrophy in AD reflects the severity and pattern of cortical neuronal damage. Correlations between regional callosal atrophy and severity of dementia indicate that interhemispheric cortico-cortical disconnection may contribute to the dementia syndrome.
Gesehen am 25.01.2021